Accountability in Government Contracts: A Measure of Performance from the Commitment-Making Officials? - Mohammad Zamroni (Hasanuddin Law Review, 2019)
Public-private partnership is an alternative defrayal which gives chances for private sectors to get engaged in financing the government’s good and service suppliers through business contract. As contracts commonly made, failure may happen while implementing the contract, known as a tort. Therefore, government contracts are conducted by Commitment-Making Officials (hereinafter, PPK), authorized to make and implement it. Thus, the accountability over the contract failure is inseparable with the authorized PPK. This study aimed to examine the accountability of PPK when failures happen in the implementation of government contract. This paper using legal research method along with statute and conceptual approaches, the finding showed that PPK were accountable both as officials and individual. As officials, their accountability is apparent when they did tort on the provision mentioned in a government contract they had signed and established. As individuals, their accountability is apparent on which they did maladministration.